Policy Evaluation Of The Halal Product Guarantee Agency (BPJPH): Impact On Producer Compliance - Anisa Tul Fitri; Ahmad Wira; Aidil Novia (Halal Research, 2025)
The existence of the Halal Product Guarantee Agency (BPJPH) is an important milestone in the halal certification system in Indonesia in accordance with the mandate of Law No. 33 of 2014 concerning Halal Product Guarantee. BPJPH has full authority in formulating policies, establishing norms, standards, procedures, and issuing and revoking halal certificates, including supervising halal auditors. However, the implementation of halal certification policies still faces significant challenges, especially in the Micro, Small and Medium Enterprises (MSMEs) sector, with certification rates only reaching around 30% of the 64 million MSMEs due to relatively high certification costs, limited access to information, and complex administrative procedures. This study aims to evaluate BPJPH policies related to halal certification and their impact on producer compliance, especially MSMEs, and identify inhibiting factors and opportunities for policy improvement. The method used is a literature study with a qualitative descriptive approach, analyzing BPJPH policy documents for the 2015-2024 period and case studies of producers involved in the halal certification process. The results showed that BPJPH policies such as Minister of Religious Affairs Regulation No. 26 of 2020 and BPJPH Regulation No. 3 of 2021 succeeded in increasing producer compliance through reducing costs and simplifying procedures. The dominant factors influencing compliance are halal market awareness, affordable costs, and halal certification.